2018
DOI: 10.3847/1538-3881/aae9f4
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Labeling Bias in Galaxy Morphologies

Abstract: We present a metric to quantify systematic labeling bias in galaxy morphology data sets stemming from the quality of the labeled data. This labeling bias is independent from labeling errors and requires knowledge about the intrinsic properties of the data with respect to the observed properties. We conduct a relative comparison of label bias for different low redshift galaxy morphology data sets. We show our metric is able to recover previous de-biasing procedures based on redshift as biasing parameter. By usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
(59 reference statements)
1
4
0
Order By: Relevance
“…We find that the morphology based on the supervised machine learning methods trained over photometric parameters demonstrates significantly less bias than morphology based on citizen-science classifiers. This conclusion is in agreement with the results by Cabrera-Vives et al (2018), who found that "this result holds even when there is underlying bias present in the training sets used in the supervised machine learning process. "…”
Section: Several Problem Points Of the Supervised Machinesupporting
confidence: 92%
“…We find that the morphology based on the supervised machine learning methods trained over photometric parameters demonstrates significantly less bias than morphology based on citizen-science classifiers. This conclusion is in agreement with the results by Cabrera-Vives et al (2018), who found that "this result holds even when there is underlying bias present in the training sets used in the supervised machine learning process. "…”
Section: Several Problem Points Of the Supervised Machinesupporting
confidence: 92%
“…Galaxy Zoo and human bias" 5 . We refer to the paper by Cabrera et al [105], where the metric for human labeling measuring in the case of low-redshift spiral/elliptical galaxies is proposed in the frame of label's comparison between experts, GZ volunteers, and ML models. Hart et al [106] developed a reliable method for defining spiral galaxies, which eliminates the redshift-dependent bias in the GZ2 volunteer's answers.…”
Section: General Results and Discussionmentioning
confidence: 99%
“…Cabrera et al [16] explained how the human labeled biases in morphological photometry-based classification could be reduced through supervised ML. This coincides with our conclusion [101], where we discuss which factors and properties of galaxies exactly affect the accuracy of supervised methods.…”
Section: Discussionmentioning
confidence: 99%